Antiviral and Immunomodulatory Properties of New Pro-Glutathione (GSH) Molecules - Fraternale, A.; Paoletti, M. F.; Casabianca, A.; Oiry, J.; Clayette, P.; Vogel, J.- U.; Jr. Cinatl, J.; Palamara, A. T.; Sgarbanti, R.; Garaci, E.; Millo, E.; Benatti, U.; et al. (Current Medicinal Chemistry, 2006)
Reduced glutathione (GSH) is present in millimolar concentrations in mammalian cells. It is involved in many cellular functions such as detoxification, amino acid transport, production of coenzymes, and the recycling of vitamins E and C. GSH acts as a redox buffer to preserve the reduced intracellular environment. Decreased glutathione levels have been found in numerous diseases such as cancer, viral infections, and immune dysfunctions. Many antioxidant molecules, such as GSH and N-acetylcysteine (NAC), have been demonstrated to inhibit in vitro and in vivo viral replication through different mechanisms of action. Accumulating evidence suggests that intracellular GSH levels in antigen-presenting cells such as macrophages, influence the Th1/Th2 cytokine response pattern, and more precisely, GSH depletion inhibits Th1-associated cytokine production and/or favours Th2 associated responses. It is known that GSH is not transported to most cells and tissues in a free form. Therefore, a number of different approaches have been developed in the last years to circumvent this problem. This review discusses the capacity of some new molecules with potent pro- GSH effects either to exert significant antiviral activity or to augment GSH intracellular content in macrophages to generate and maintain the appropriate Th1/Th2 balance. The observations reported herein show that pro-GSH molecules represent new therapeutic agents to treat antiviral infections and Th2-mediated diseases such as allergic disorders and AIDS.
Keywords: Th1/Th2 responses